Actividad física y calidad de vida en estudiantes de décimo ciclo de la carrera de medicina de la Universidad Nacional de Loja - Calva Reyes, Wilson Fabian (2023)
Sedentary lifestyle has become a disease of the 21st century and its systemic effects, which may include cardiovascular, as well as metabolic and psychological effects, are important causes of obesity, morbidity, mortality and quality of life in the general population. Although physical activity is a completely modifiable factor, it is the most cost-effective and efficient way to control the secondary complications of sedentary lifestyles such as obesity, arterial hypertension and type II diabetes, thus improving people's quality of life. The research was carried out with the objective of determining the relationship between physical activity and quality of life in tenth cycle students of the medical career at Universidad Nacional de Loja during September 2021 - April 2022, with a quantitative approach of transversal cohort, It had the participation of 70 students who met the inclusion and exclusion criteria, to whom two Likert-type scales were applied, obtaining that 91.43% of the students had a moderate practice of physical activity, 71.43% have a medium quality of life and 28.57% have a high quality of life. We conclude that in this population there is a significant relationship 0.00 l (p < 0.420) between physical activity and quality of life being a positive relationship